2021
DOI: 10.7717/peerj-cs.358
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: a new deep learning computer-aided model for classification

Abstract: Chest X-ray (CXR) imaging is one of the most feasible diagnosis modalities for early detection of the infection of COVID-19 viruses, which is classified as a pandemic according to the World Health Organization (WHO) report in December 2019. COVID-19 is a rapid natural mutual virus that belongs to the coronavirus family. CXR scans are one of the vital tools to early detect COVID-19 to monitor further and control its virus spread. Classification of COVID-19 aims to detect whether a subject is infected or not. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…To detect COVID-19, several approaches have been proposed based on deep learning techniques. In Elzeki et al (2021) , the authors used three pre-trained CNN models based on three different chest X-ray sets. Also, in Kamal et al (2021) , the authors used eight pre-trained CNN models to detect COVID-19 from chest X-rays.…”
Section: Related Workmentioning
confidence: 99%
“…To detect COVID-19, several approaches have been proposed based on deep learning techniques. In Elzeki et al (2021) , the authors used three pre-trained CNN models based on three different chest X-ray sets. Also, in Kamal et al (2021) , the authors used eight pre-trained CNN models to detect COVID-19 from chest X-rays.…”
Section: Related Workmentioning
confidence: 99%
“…These methods are an appropriate step to employ in all statistical/econometric modeling. Furthermore, there exists a potential use in machine, deep, and statistical learning models [39,[59][60][61]. Future research will consider other variables and relationships, such as production linkages and employment effects of the COVID-19 pandemic phenomena.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“… Elzeki et al (2021) presented a new deep learning computer-aided scheme for rapid and seamless classification of COVID-19. Consisting of three separate COVID-19 X-ray datasets, the study presented the COVID Network (CXRVN) model for assessing grayscale chest X-ray images.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of the performed experiments showed that the new multi-model and multi-data approach achieved improved performance over the traditional machine learning models. Elzeki et al (2021) presented a new deep learning computer-aided scheme for rapid and seamless classification of COVID-19. Consisting of three separate COVID-19 X-ray datasets, the study presented the COVID Network (CXRVN) model for assessing grayscale chest X-ray images.…”
Section: Introductionmentioning
confidence: 99%